Online Learning during Covid-19 Pandemic in Developing Countries: Does it run well? - Jhon, Winarni; Mustadi, Ali; Zubaidah, Enny (Jurnal Pendidikan Progresif, 2020)
Online Learning during Covid-19 Pandemic: Does it run well? Objectives: This article was aimed to identify the challenges that occur in the implementation of online learning during Covid-19 pandemic in several developing countries from teachers and students perspectives. Methods: We applied a systematic review of literature using search protocol based on the PRISMA recommendation statement. The initial step of the study was the formulation of the research problem, then search of relevant research results from national and international journals with the keyword “Covid online learning” on ScienceDirect, Directory of Open Access Journals and Google Scholar search engine. Then, an analysis of relevant research results was carried out in relation to challenges in the implementation online learning during Covid-19 pandemic in all level of educations. Findings: As a result, teachers mostly face challenges on the planning, implementation and evaluation of online learning. Technological challenges are the main challenges that students face in online learning during Covid-19 pandemic. Conclusion: There should be further investigations to identity challenges that teachers and students face in online learning. Keywords: online learning, challenges, covid-19, teachers, students DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202006